Tunable graphene oxide reduction and graphene patterning at room temperature on arbitrary substrates. (November 2016) - Deng, Ning-Qin; Tian, He; Ju, Zhen-Yi; Zhao, Hai-Ming; Li, Cheng; Mohammad, Mohammad Ali; Tao, Lu-Qi; Pang, Yu; Wang, Xue-Feng; Zhang, Tian-Yu; Yang, Yi; Ren, Tian-Ling
Abstract: Over the past decade, reports of graphene-based devices have increased exponentially due to the superior characteristics and unique advantages that graphene introduces. However, the cost-effective growth and patterning of graphene is always a challenge for large-scale graphene-based device applications. Here we report a universal method based on one-step laser scribing technology for quick synthesis and patterning of large-scale multi-layer graphene films from graphene oxide films using a 650 nm commercial laser on arbitrary substrates. Moreover, by tuning the laser power, three distinct regions are found: growth, transition and etch regions. SEM, optical microscopy, Raman spectroscopy, electrical conductance testing, and transmittance measurements confirm the presence of three such regions. These tests show that the reduction of GO happens at low power and the gasification of LSG into CO2 happens at high power. Furthermore, a theoretical model is established to analyse the thickness changes under different laser power. This laser processing method could significantly simplify the processing steps and reduce the cost for the fabrication of graphene-based devices. This work also demonstrates promising applications for scalable manufacturing of graphene-based devices using one-step laser processing at standard temperature and pressure.